2008
DOI: 10.3349/ymj.2008.49.5.860
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Marginal Zone Lymphoma Occurring along the Trachea and Central Airway

Abstract: Extranodal marginal zone lymphoma is a low-grade B cell lymphoma that presents with an indolent clinicopathologic nature. Although this tumor can occur in various sites, including the gastrointestinal tract and lungs, it develops and spreads extremely rarely along the trachea and central airway. We report a case of extranodal lymphoma of mucosa-associated lymphoid tissue with tracheobronchial involvement. An 83-year-old woman presented with a cough and dyspnea. Bronchoscopic evaluation confirmed diffuse, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…However our patient presented with the lesions localized from the trachea to the left main bronchus. This case has characteristics in common with the case reported by Kang et al [5], whose case showed multiple, variable-sized nodules causing bronchial narrowing from the proximal trachea to bronchi of both lungs, including the carina. The lesions of both of these cases are systemic disseminated.…”
Section: Discussionsupporting
confidence: 84%
“…However our patient presented with the lesions localized from the trachea to the left main bronchus. This case has characteristics in common with the case reported by Kang et al [5], whose case showed multiple, variable-sized nodules causing bronchial narrowing from the proximal trachea to bronchi of both lungs, including the carina. The lesions of both of these cases are systemic disseminated.…”
Section: Discussionsupporting
confidence: 84%
“…There are other previous case reports which have shown female predominancy (18, 20). All patients were female in our series.…”
Section: Discussionmentioning
confidence: 81%
“…There is one case report in the literature that describes diffuse narrowing of the tracheobronchial tree with endobronchial nodularities of extranodal marginal zone lymphoma, occurring along the trachea and central airway (20). However, to the best of our knowledge, BALT lymphoma manifesting as diffuse wall thickening in the central airway on CT has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Both primary and secondary tracheobronchial disease most commonly manifest as a soft-tissue nodular or polypoid mass (Fig 10a). Diffuse polypoid or broad-based lesions are seen in a minority of cases (Figs 8, 10b) (2,37,38). Postobstructive atelectasis or consolidation may be present where there is significant airway narrowing (Fig 10b).…”
Section: Ct Findingsmentioning
confidence: 99%